Successful extracorporeal membrane oxygenation for postoperative cardiopulmonary failure in newborns with congenital diaphragmatic hernia: case reports and literature reviews - Hong, Song-Ming; Chen, Xiu-Hua; Zhou, Si-Jia; Hong, Jun-Jie; Zheng, Yi-Rong; Chen, Qiang; Huang, Jin-Xi (Frontiers in Pediatrics, 2023)
Congenital diaphragmatic hernia (CDH) is a structural defect caused by inadequate fusion of the pleuroperitoneal membrane that forms the diaphragm, allowing peritoneal viscera to protrude into the pleural cavity. Up to 30% of newborns with CDH require ECMO support. As with all interventions, the risks and benefits of ECMO must be carefully considered in these patients. Cardiopulmonary function has been shown to worsen rather than improve after surgical CDH repair. Even after a detailed perioperative assessment, sudden cardiopulmonary failure after surgery is dangerous and requires timely and effective treatments. Three cases of cardiopulmonary failure after surgical CDH treatment in newborns have been reported. ECMO support was needed for these three patients and was successfully discontinued. We report our treatment experience.